(untitled) (Emancipação, 2024)
This article reports on the production and circulation of meaning in the formative process developed for Socio-Education Policy servants in the State of Paraná, since the creation of the National School of Socio-Education and the State Management Nucleus. The development of the text was based on the documental analysis of the institutional reports, articulated with the professional practice and the unsystematic observation carried out by the authors. The data source is guided by an analysis of primary documents, and the analytical cut is located in the period from 2015 to 2017. Initially, in a first stage, the authors deliberate by reading the institutional data published by federal and state bodies responsible for staff training. The objective was to find sources and, in them, the documents necessary for the production of the research and the article. By obtaining information from state publications, we began the process of describing and analyzing the training cycles.